Experimental detection of the Penang bridge vibration with real time kinematic gps - Mat Amin, Zulkarnaini (2003)
Vibration and dynamic deflection of bridge is an important aspect for bridge security evaluation. With the advance in sensor systems, data acquisition, data communication and computational methodologies, instrumentation-based monitoring has been a widely accepted technology to monitor and diagnose structural health and conditions for civil engineering structures such as bridges. For the health monitoring of bridges, sensors, which are reliable and robust, portable, non-destructive and automated such as Global Positioning System (GPS), are well suited. In addition, GPS also offer an opportunity for real or near real-time monitoring. This paper reports on the first experimental realization of the bridge evaluation using real time kinematic (RTK) GPS technique through a series of tests conducted on the Penang Bridge. It gives details of the methodology and a strategy for detecting vibration of the bridge. This paper also focuses on applying frequency domain method to bridge vibration. Finally conclusions are drawn with regard to the feasibility of the GPS in a bridge vibration measurement.